2011
DOI: 10.1021/ie201062p
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Profiles and Process Performances of Sponge Packings As Compared to Spherical Catalysts in the Oxidation of o-Xylene to Phthalic Anhydride

Abstract: The oxidation of o-xylene to phthalic anhydride was carried out in a pilot plant with a tubular reactor in order to investigate the heat transfer properties of different types of catalytic fixed beds through analysis of the temperature profiles arising upon polytropic o-xylene conversion. Ceramic sponges of different materials and pore densities were compared to a packed bed of spheres, all of which were coated with novel flame-made vanadia/titania catalyst nanoparticles. The temperature profiles were smoother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…It is worth mentioning here that the different supports do not influence the catalytic behavior of the flame-made catalyst by any kind of chemical interaction, as it was shown in a previous publication. 18 2.1. Catalyst Preparation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth mentioning here that the different supports do not influence the catalytic behavior of the flame-made catalyst by any kind of chemical interaction, as it was shown in a previous publication. 18 2.1. Catalyst Preparation.…”
Section: Methodsmentioning
confidence: 99%
“…Sponges made of materials with high thermal conductivity (e.g., silicon carbide) were found to improve heat removal from the catalyst bed to such an extent that the STY of PA could be doubled as compared to a fixedbed of ceramic spheres coated with the same V 2 O 5 /TiO 2 active material. 18 To predict and to improve the performance of a catalytic reactor at industrially relevant conditions, the knowledge of the reaction kinetics is indispensible. In the case of the oxidation of o-xylene to PA, several kinetic studies have been published already.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Foams offer several advantages compared to the other two structures: higher radial mass flow, higher radial heat exchange, higher tortuosity of the flow resulting in more interesting fluid dynamics, lower pressure drop, and a higher geometrical porosity. [26] The catalyst carriers were coated with a vanadia/titania catalyst and fitted in a tube reactor. [1] The use of SiÀSiC foams, compared to other materials, is justified for reactions that take place in acid or basic conditions or reactions for which high thermal conductivity of the catalyst carrier is necessary.…”
Section: Catalyst Carriersmentioning
confidence: 99%
“…It is widely recognized that spatially structured reactors are at the very heart of process intensification [1,2] and it has been shown that significant enhancement of radial heat transfer rates in multitubular catalytic reactors with external cooling can be achieved if the random packings of catalyst pellets are replaced by structured catalysts with thermally connected, highly conductive foams [3][4][5][6]. Nevertheless, some issues still exist that prevent the application of this technology at the industrial scale.…”
Section: Introductionmentioning
confidence: 99%